-1(logex)^-2 x (1/x)

= -1/(x(logex)^2)

Sorry if my terminology isn't clear- im in australia and the syllabus is different here (just had my finals and im depressed over a poor effort in my most important exam...trying to find some solace by going over everything and brushing up my math skills...just can't believe how much effort i put in to make so many silly mistakes on the day...)

]]>Taking u = 1 and v = ln x means that u' = 0 and v' = 1/x, so (u/v)' would be **-1/x(ln x)²**.

There may be a simpler way of doing that that gives a simpler answer, but I'm sleepy so I can't see one.

1 / ln x ????????????????????????????????????????????

]]>